1995
DOI: 10.1016/0029-7844(95)00271-r
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and biomolecular aspects of papillomatosis of the vulvar vestibule in relation to human papillomavirus

Abstract: Papillomatosis of the vulvar vestibule is not associated with HPV and should be considered a paraphysiologic formation of the vulvar epithelium. The diagnosis of vulvar HPV infection should be avoided in the absence of more explicit clinical-histologic evidence, with no need for biopsies or unnecessary treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Early reports suggested that human papilloma virus (HPV) plays a major role in the pathogenesis of vulvar vestibulitis [50]. However, this could not be confirmed by studies using molecular techniques [51,52]. Vulvodynia associated with HPV DNA is clinically identical to vulvodynia without HPV DNA, suggesting that HPV does not cause vulvodynia [53].…”
Section: Vulvodyniamentioning
confidence: 89%
“…Early reports suggested that human papilloma virus (HPV) plays a major role in the pathogenesis of vulvar vestibulitis [50]. However, this could not be confirmed by studies using molecular techniques [51,52]. Vulvodynia associated with HPV DNA is clinically identical to vulvodynia without HPV DNA, suggesting that HPV does not cause vulvodynia [53].…”
Section: Vulvodyniamentioning
confidence: 89%
“…This condition is characterized by multiple millimetric papillae of the vestibule and lower third of labia minora. This entity is a normal anatomical variant of the vulva but is commonly mistaken for human papillomavirus (HPV) condyloma [15]. In a prevalence study performed in the UK, 1% of women showed vestibular papillomatosis, although other authors have found the prevalence to range between 5.1% and 33%.…”
Section: Vestibular Papillomatosismentioning
confidence: 96%
“…Neben den typischen blumenkohlartigen Kondylomen findet man bei den betroffenen kleinen Mädchen das Bild der Vulvapapillomatose: kleine Papillen,bevorzugt im Bereich des Vestibulums und periurethral, die grundsätzlich als paraphysiologische Formation des Vulvaepithels angesehen werden müssen, und in denen nur in 6% HPV-DNA nachgewiesen werden kann [5]. Neben den typischen blumenkohlartigen Kondylomen findet man bei den betroffenen kleinen Mädchen das Bild der Vulvapapillomatose: kleine Papillen,bevorzugt im Bereich des Vestibulums und periurethral, die grundsätzlich als paraphysiologische Formation des Vulvaepithels angesehen werden müssen, und in denen nur in 6% HPV-DNA nachgewiesen werden kann [5].…”
Section: Genitale Hpv-läsion Im Kindes-und Jugendalterunclassified